PERANCANGAN JARINGAN KOMPUTER RT/RW NET MENGGUNAKAN JALUR KOMUNIKASI POWER LINE (PLC) DI PERUMAHAN TAMAN BERDIKARI SENTOSA - Prasetyo Adi Nugroho (Institut Teknologi dan Bisnis Swadharma, 2022)
RT/RW Net is a non-governmental computer network within the scope of RT/RW. Building an RT/RW Net in the Taman Berdikari Sentosa housing estate is a concept where several computers in a housing or block can be connected and can share data and information, express opinions, conduct polls, and even elect RT/RW. The RT/RW net network will be built using a power line (PLC) communication line. Power Line Communication (PLC) is a technology that supports computer networks on a small scale such as a LAN, RW/RW net, which can provide convenience in installation tasks to produce high-speed computer networks. In principle, the Powerline used functions as a medium that converts digital data to electric current so that the data can be sent via a power cable. Building an RT/RW Net network using Power Line is no different from building an RW/RW Net in general. The difference only lies in the data transmission media used, Power Line uses electric cables while RT/RW Net generally uses cables such as UTP, Fiber Optic, Coaxial, and wireless networks